PENGARUH PENDAMPINGAN PASTORAL UNTUK MENINGKATKAN RELIGIUSITAS WARGA BINAAN KASUS PELECEHAN SEKSUAL TERHADAP ANAK DI LAPAS KLAS IIA AMBON - Imelda Ch Pocerattu (IAKN Ambon, 2018)
Penitentiary or abbreviated prisons is an institution of criminal justice sub-system has a strategic function as the implementation of imprisonment as well as a place of coaching for prisoners are required to be able to implement a penitentiary system. This is mandated in Law no. 12 Year 1995 About Pemasyarakatan that aims to establish prisoners built to be a whole person, realize mistakes, improve themselves, and not repeat the crime so that it can be accepted back by the community, can actively play a role in development, and can live as a natural citizen is good and responsible. For the citizens who are undergoing their criminal term in prison must face various obstacles. Living a life in prisons is the most extreme change of life. Many difficult people are faced with the fact that they have to live and adapt in prisons. The weight of the burden of life often makes them feel hopeless, sad prolonged, do not have the spirit of life, even the very extreme they no longer believe in kemakaKuahKodipta The Creator. In these situations, the people in need are pastoral care so that they can repent of the sins committed and the new life according to the will of God. Thus pastoral care has a very important influence in guiding the lives of the targeted people, so as not to commit the same mistake (sin) and improve life for the better according to the will of God. With pastoral care, of course, it can enhance the deep appreciation of one's faith in the religion it embraces, or in other words increases the religiosity of the assisted citizens.